VOCABULARY MASTERY AND ITS INFLUENCE ON STUDENTS’ DESCRIPTIVE WRITING: A CORRELATION RESEARCH - Elsa Kurnia; Gaya Tridinanti; Nita Ria (Didascein : Journal of English Education, 2025)
This research aimed to determine the correlation between tenth-grade students' vocabulary mastery and their descriptive writing ability, and to determine the contribution of students' vocabulary mastery to their descriptive writing ability. The research design was a correlational study, and the population consisted of 450 tenth-grade students from 14 classes at SMA N 10 Palembang. To select the sample of this research, purposive sampling was implemented. There were 72 students as a sample from classes X.7 and X.8. The obtained data were analyzed using correlation and regression analyses. The data were obtained from writing ability and vocabulary mastery tests. The results indicated that the significant coefficient between writing ability and vocabulary mastery was 0.802, which was higher than the alpha value of 0.05. It means that vocabulary mastery and writing ability were not correlated. At that point, the correlation coefficient was 0.030, which placed it in the low category of the correlation coefficient. Subsequently, regression analysis revealed that the R-value was 0.066 and its coefficient of determination (R-squared) was 0.004. It concluded that the contribution of vocabulary mastery to writing skill was only 0.04%. In conclusion, the r-value was less than the alpha-value (0.802 > 0.05), indicating that there was no significant relationship between writing ability and vocabulary mastery. There was no contribution or interaction effect on vocabulary mastery or writing ability, since the R-value was 0.004, or only 0.04%.